A safe house [compact disc, unabridged] - Woods, Stuart (Woods, Stuart. Stone Barrington novel (Sound recording), 2022)
Stone Barrington is looking forward to some quiet time in NYC, but he is asked to transport top-secret cargo across the Atlantic. Taking on the challenge, Stone flies off, unaware of what he is bringing with him.